TIPOMORFOLOGI ARSITEKTUR BANGUNAN PECINAN DI KESAWAN MEDAN - Rudiansyah Rudiansyah (Berkala Arkeologi Sangkhakala, 2021)
Most of the buildings in Kesawan-Medan still maintain the Dutch-Chinese architecture of the transitional period or the Transitional architecture, although the awareness to preserve this historical heritage is still low. Furthermore, there is no regulation limiting changes that may be made, yet it has not been designated as a Cultural Conservation Building. This situation raises fears of losing track of the original building. This paper intends to explain the typomorphological characteristics of the Chinatown building architecture in Kesawan-Medan. The method used is desk research on research reports, various sources of books, and journals. The theory used is the theory of area morphology and building typology from Andre Loeckx and Markus Zahnd. The general condition of the building has not lost its original form. Renovations were carried out within the limits of repainting, repairing damaged elements, and changing functions. Typomorphology is evident from the materials used and their layout. Building materials used are from the surrounding environment, such as bricks, tile roofs, and windows. The layout of the building is in the residential emplacement area of the city center, with a flat topography in the tropical wet climate of Indonesia. Permukiman kesawan Medan sebagian besar masih mempertahankan arsitektur bangunan Belanda-China periode peralihan atau arsitektur Transisi, walaupun kesadaran pelestarian peninggalan bernilai sejarah masih minim. Belum ada peraturan batasan perubahan yang boleh dilakukan dan belum ditetapkan sebagai Bangunan Cagar Budaya. Keadaan ini menimbulkan kekhawatiran akan kehilangan jejak bangunan aslinya. Tulisan ini bermaksud untuk menjelaskan karakteristik tipomorfologi arsitektur bangunan pecinan di kesawan Medan. Metode yang digunakan adalah desk research terhadap laporan hasil penelitian, berbagai sumber buku dan jurnal. Menggunakan teori morfologi kawasan dan tipologi bangunan dari Andre Loeckx dan Markus Zahnd. Kondisi bangunan secara umum belum kehilangan bentuk aslinya. Renovasi dilakukan dalam batas pengecatan ulang, perbaikan elemen yang rusak, dan perubahan fungsi. Tipomorfologi khasnya tampak dari bahan yang digunakan dan tata letaknya. Bahan bangunan dari lingkungan sekitar, seperti bata, keramik atap genting dan jendela. Tata letak bangunan berada di kawasan emplasemen permukiman pusat kota, dengan topografi lahan datar dalam lingkungan iklim tropis basah Indonesia.